COMPARATIVE STUDY OF KASISADI GHRITA AND JATYADI TAIL IN THE MANAGEMENT OF PARIKARTIKA WITH SPECIAL REFERENCE TO FISSURE-IN - ANO - Mamta Gopalrao Mate,; D. N. Farande,; S.Dudhalwar,; Vinay Mukeshkumar Pandey,; Anita Bombarde, (International Journal of Applied Ayurved Research, 2019)
Background: Acharya Sushruta has described aetiology and management of Parikartika in details. Signs and symptoms of the disease fissure-in-ano can be co-related with Parikartika according to Ayurveda. There is sharp cutting pain in anal region. In Parikartika, Teevra shoola, bleeding is seen sometimes with stool or after defecation, similarly pain and creepy blood discharge are seen in Fissure-in-ano. Objective: To assess the efficiency of Kasisadi Ghruta local application and to compare the efficacy of Kasisadi Ghruta and Jatyadi Tail in the Management of Parikartika with special reference to fissure-in - ano. Methods: The patient having classical signs and symptoms of Parikartika (fissure in ano) having Age group – 20 to 60 years was included in the study. Experimental group was treated with Kasisadi Ghruta and Control group treated with Jatyadi Tail. Patients were advised to apply locally at the site of fissure in ano for 28 days. Results & Conclusion: Kasisadi Ghruta and Jatyadi tail are highly significant in symptoms Kartanavat Vedana, Bleeding per rectum, Itching in anus, Burning, Discharge, Inflammations, Tenderness, Sphincter spasm except Sentinel tags. Kasisadi Ghruta and Jatyadi tail found equally effective in Fissure-in-ano.